Effects of LiBa2Ta5O15 Addition on the Dielectric and Ferroelectric Properties of BaTiO3 Ceramics. (19th February 2016) - Wu, Yurong; Pu, Yongping; Zhao, Jiaojiao; Zhang, Panpan
Abstract : (1- x )BaTiO3 - x LiBa2 Ta5 O15 ( x = 0, 0.002, 0.004, 0.006, 0.008, 0.010) ceramics were prepared by the solid state method. The effect of LiBa2 Ta5 O15 content on dielectric and ferroelectric properties was investigated. When x > 0.004, a secondary phase LiBa2 Ta5 O15 was detected. With the increase of LiBa2 Ta5 O15 content, the dielectric constant near Curie temperature was dramatically suppressed. The dielectric loss meet tanδ ≤ 0.02 when 0.002 ≤ x ≤ 0.004. Obvious diffusion phenomenon was observed at x = 0.004. The hysteresis loops became narrower regularly with the increasing amount of LiBa2 Ta5 O15 content, which eliminated ferroelectric properties and changed to be a low loss dielectric material. It will be a promising candidate for high temperature stability dielectric materials.